Dual wavelength single longitudinal mode Ytterbium-doped fiber laser using a dual-tapered Mach-Zehnder interferometer - Ahmad, Harith; Mat Salim, Muhammad Aizi; Azzuhri, Saaidal Razalli; Zulkifli, Mohd Zamani; Harun, Sulaiman Wadi (Springer, 2015)
This paper describes a dual wavelength single longitudinal mode (SLM) demonstration for a proposed ytterbium-doped fiber laser. A dualtapered Mach-Zehnder interferometer (MZI) was inserted into the laser ring cavity setup to ensure a stable dual wavelength and SLM operation. The consequent dual wavelength lasing operation had a wavelength spacing of 0.94 nm and a side mode suppression ratio (SMSR) of 50 dB, with the linewidth of this setup measured as 294.15 kHz. A stability test allowed for a measurement of max power fluctuation as less than 0.8 dB for each wavelength and which was indicative of a stable dual wavelength operation.